2017
DOI: 10.56093/ijas.v87i3.68596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrient management and drought mitigating practices on performance of rainfed chickpea (Cicer arietinum)

Abstract: The investigation aimed to study the effect of integrated nutrient management and drought mitigating practices on rainfed chickpea (Cicer arietinum L.) on sandy clay loam soil at Varanasi in winters of 2012-13 and 2013-14. The treatment consisted of combinations of four integrated nutrients levels in main plot and five drought mitigating practices including control in sub-plot. The growth and yield were significantly influenced by different integrated nutrients during both the years. Application of 100% RDF + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Higher seed and haulm yield with increased fertilizer dose had resulted in higher net returns with 125% RDF + MC. Dewangan et al (2017) also reported similar results with respect to improved haulm yield in chickpea with integrated nutrient management.…”
Section: Treatmentssupporting
confidence: 55%
“…Higher seed and haulm yield with increased fertilizer dose had resulted in higher net returns with 125% RDF + MC. Dewangan et al (2017) also reported similar results with respect to improved haulm yield in chickpea with integrated nutrient management.…”
Section: Treatmentssupporting
confidence: 55%